FRACTIONATION OF PHENOLIC COMPOUNDS FROM KAFFIR LIME (Citrus hystrix) PEEL EXTRACT AND EVALUATION OF ANTIOXIDANT ACTIVITY - Yusak Adi Wijaya; Daniel Widyadinata; Wenny Irawaty; Aning Ayucitra (Reaktor, 2017)
Side effects of drug-based treatment observed in patients during degenerative diseases treatments has directed towards to the identification of plants with antioxidant activity. Kaffir lime peel was selected in this study. This work was aimed to investigate the effect of solvent (hexane, ethyl acetate and n-butanol) polarity on the fractionation of ethanolic crude extract and assess its antioxidative property by DPPH radical scavenging assay. The results show semi polar solvent of ethyl acetate exhibited the best solvent to extract phenolic compounds from ethanolic kaffir lime peel with total phenolic content detected was 0.12 mg Gallic Acid Equivalent/mg. The employment of solvents possessing different polarity resulted several fractions, i.e. hexane, ethyl acetate, n-butanol and residue with different type of phenolic compounds in each fraction. Accordingly, each fraction exhibited different antioxidant activity against free radical compound of DPPH. The N-butanol fraction demonstrated the strongest activity which is shown by lowest IC50 value among the fractions tested. The fraction of n-butanol exhibited the IC50 value of 0.44 mg/mL which means that only 0.44 mg of the fraction/mL is required to inhibit the neutralization of DPPH by 50%. Phenolic identification by High Performance Liquid Chromatography indicates the different phenolic compounds in each fraction that contribute to antioxidative property to different extent. Further investigation to identify these phenolic compounds will lead to further development of kaffir lime as natural antioxidant to treat specific degenerative diseases.